2005
DOI: 10.1007/s00430-005-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant enolase from Anisakis simplex is differentially recognized in natural human and mouse experimental infections

Abstract: A 1,963-bp cDNA was isolated from an Anisakis simplex cDNA library by immunoscreening with a hyperimmune rabbit serum raised against a crude extract of A. simplex L3 larvae. The open reading frame encodes a putative protein of 436 amino acid residues, which exhibits high similarity (70-80%) to enolase molecules from various other organisms, including helminth parasites. After subcloning and expression of the A. simplex cDNA in PGEX-4T-3, the resulting glutathione S-transferase fusion protein, purified by gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Up to date, investigations on the structure and function of parasite enolases focus on protozoa, such as plasmodium Pal-Bhowmick et al 2004Read et al 1994), toxoplasma (Dzierszinski et al 2001;Ferguson et al 2002;Kibe et al 2005), Eimeria tenellum (Labbé et al 2006), Entamoeba histolytica (Hidalgo et al 1997), Trichomonas vaginalis (Mundodi et al 2008), Trypanosoma brucei (Hannaert et al , 2007da Silva Giotto et al 2003), Leishmania mexicana (Vanegas et al 2007;Quiñones et al 2007) as well as some helminthes, such as schistosome (Liu et al 2009;Pérez-Sánchez et al 2008;Ramajo-Hernández et al 2007;Waine et al 1993), Fasciola hepatica (Bernal et al 2004), Echinostoma caproni (Marcilla et al 2007), filaria (Jolodar et al 2003), Anisakis simplex (Rodríguez et al 2006), and Trichinella spiralis (Nakada et al 2005). As for enolase from tapeworm, no investigation was reported, except for an enolase from T. asiatica (Huang et al 2008b), which was cloned in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, investigations on the structure and function of parasite enolases focus on protozoa, such as plasmodium Pal-Bhowmick et al 2004Read et al 1994), toxoplasma (Dzierszinski et al 2001;Ferguson et al 2002;Kibe et al 2005), Eimeria tenellum (Labbé et al 2006), Entamoeba histolytica (Hidalgo et al 1997), Trichomonas vaginalis (Mundodi et al 2008), Trypanosoma brucei (Hannaert et al , 2007da Silva Giotto et al 2003), Leishmania mexicana (Vanegas et al 2007;Quiñones et al 2007) as well as some helminthes, such as schistosome (Liu et al 2009;Pérez-Sánchez et al 2008;Ramajo-Hernández et al 2007;Waine et al 1993), Fasciola hepatica (Bernal et al 2004), Echinostoma caproni (Marcilla et al 2007), filaria (Jolodar et al 2003), Anisakis simplex (Rodríguez et al 2006), and Trichinella spiralis (Nakada et al 2005). As for enolase from tapeworm, no investigation was reported, except for an enolase from T. asiatica (Huang et al 2008b), which was cloned in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…A UniZAP XR cDNA library prepared from third‐stage A. simplex larvae (17) was immunoscreened with mAb UA3. Positive plaques were purified by repeated cycles of immunoscreening and transformed into phagemid clones by helper phage rescue (18).…”
Section: Methodsmentioning
confidence: 99%
“…Enolase appears to be a major antigenic protein in several organisms, including parasitic protozoa like Eimeria tenella and Plasmodium falciparum (28,54), yeasts like Candida albicans (45,46), nematodes like Trichinella spiralis (37), and also trematodes like Schistosoma bovis (42), but its immunogenicity is controversial. A recent study was unable to detect antienolase IgE in sera from human patients infected with Anisakis simplex, suggesting an insufficient antigen presentation to induce anti-enolase antibodies in natural Anisakis infections (49). Moreover, Morphew et al (36) have observed that enolase accumulates in the ESP of F. hepatica during the incubation process, even when the trematode is dead (36).…”
Section: Vol 15 2008 Lap As An Immunodominant Antigen In Human Fascmentioning
confidence: 99%